Comparison of New Topical Treatment (Curcumine viscous solution 30% ) For Recurrent Herpes Labialis (RHL) - Maha T Al-Saffar (University of Mosul, College of Dentistry, 2009)
Aims: To determine the therapeutic effect of viscaus solution of curcumine 30% , as a topical treatment of RHL in comparison with the traditional antiviral agent " acyclovir ". Materials and methods: A total of 120 patients (100 female, 20 male) with RHL divided into four groups: Group I: Fifty patients used viscous solution of curcumine 30% topically. Group II: Thirty patients used viramed "acyclovir" cream topically. Group III: Twenty five patients used glycerol topically "control positive group".Group IV: Fifteen patients without treatment "control negative group". Results: Female were more affected than male with RHL (83.3% female, 16.3% male) with high percentage of association between highly stressed events and RHL. The results also showed significant differences between size of lesion, duration of healing and pain in patients using viscous curcumine solution topically and patients received viramed cream and patient received no treatment. The patients group which received glycerol "control positive" showed a significant differences in duration of healing compared with group I and group II. While, patients group which received viramed topically showed no significant differences compared with group III and IV in related to duration of pain and show significant difference with group I, III and IV in relation to duration of healing. Conclusions: Topical application of viscaus carcumine solution 30% showed a good effective response on RHL compared with other antiviral agent with the lower percentage of adverse effect, and further study for its effect on other oral lesion may be recommended.